Anatomy & Yoga. Muscles in action - Coll, M. P. (2018)
Anatomy & Yoga is a complete work that introduces the yoga tradition from a practical and scientific point of view. It is aimed at students, teachers, people who practice yoga, and those who want to familiarize themselves with this millennia-old practice. Combining science and tradition, this book explains the history of yoga—the classical texts and their traditions—50 classical yoga postures (asanas) as well as variations and adaptations for safe practice; proper breathing, including basic breathing exercises (pranayama); and the important yoga aspect of inner development. Along with clear and informative content, this book contains an anatomical and physiological description of the human body and relevant information about the energetic anatomy—in other words, an explanation of the human body and the chakras. For each asana, the precautions and the gained physical, psychological, and energetic benefits are listed. In addition, each asana is accompanied by images illustrating the exercise and anatomical drawings showing in detail the main muscles used in each posture. With information on relaxation practice, mudras, and meditation, Anatomy & Yoga allows you to penetrate a little deeper into yoga and, starting from the physical discipline, helps you experience yoga as a spiritual discipline. Klappentext